2013
DOI: 10.1002/mnfr.201200593
|View full text |Cite
|
Sign up to set email alerts
|

A metabolite of daidzein, 6,7,4′‐trihydroxyisoflavone, suppresses adipogenesis in 3T3‐L1 preadipocytes via ATP‐competitive inhibition of PI3K

Abstract: Our results suggest that 6,7,4'-THIF suppresses adipogenesis in 3T3-L1 preadipocytes by directly targeting PI3K. Soy isoflavones like 6,7,4'-THIF may have potential for development into novel treatment strategies for chronic obesity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 47 publications
1
33
0
Order By: Relevance
“…Endogenous β-glucosidase in soybean is reported to be able to convert isoflavone glucosides into aglycones, in agreement with the increase in the amount of isoflavone aglycones and decrease in isoflavone glucosides during soybean soaking in water and processing [17]. Previous studies have demonstrated that isoflavones have anti-obesity or anti-adipogenesis function by suppressing obesity-related transcription through a feedback mechanism on adiponectin, adipoR1, adipoR2, and 5′ adenosine monophosphate-activated protein kinase (AMPK), or by targeting the PI3K/AKT signaling pathway [18,19]. Therefore, we suggest that isoflavone-rich BSK extract may also have similar functions against adipogenesis or insulin resistance.…”
Section: Resultsmentioning
confidence: 53%
“…Endogenous β-glucosidase in soybean is reported to be able to convert isoflavone glucosides into aglycones, in agreement with the increase in the amount of isoflavone aglycones and decrease in isoflavone glucosides during soybean soaking in water and processing [17]. Previous studies have demonstrated that isoflavones have anti-obesity or anti-adipogenesis function by suppressing obesity-related transcription through a feedback mechanism on adiponectin, adipoR1, adipoR2, and 5′ adenosine monophosphate-activated protein kinase (AMPK), or by targeting the PI3K/AKT signaling pathway [18,19]. Therefore, we suggest that isoflavone-rich BSK extract may also have similar functions against adipogenesis or insulin resistance.…”
Section: Resultsmentioning
confidence: 53%
“…A kinase assay was performed as previously described [Seo et al, ]. Briefly, active PI3K protein (100 ng) was incubated with HST, at volumes of 20, 40, and 80 µM, or PI3K inhibitor LY294002 (20 µM), before 20 µl phosphatidylinositol (0.5 mg/ml; Avanti Polar Lipids, Alabaster, AL) was added.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, Seo et al reported that 6-OHD at high concentrations (40 to 80 μM) suppressed adipogenesis in 3T3-L1 preadipocytes by directing targeting phosphatidylinositol 3-kinase (PI3K) [70]. In contrast, Chen et al recently reported that 6-OHD at low concentrations (10 to 20 μM) significantly promoted 3T3-L1 preadipocytes differentiation [71].…”
Section: Bioactivity Of Ohd and Ohgmentioning
confidence: 99%